2019
DOI: 10.1002/anie.201910898
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Synthesis of Oxa‐Bridged Oxazocines through a Catalytic RhII/ZnII Relay [4+3] Cycloaddition Reaction

Abstract: Oxa‐bridged oxazocines bearing three chiral carbon centers were synthesized efficiently through a bimetallic catalytic asymmetric tandem reaction of β,γ‐unsaturated α‐ketoesters with diazoimides. The process contained a rhodium‐promoted in situ generation of isomünchnone from diazoimide decomposition, and a [4+3]‐cycloaddition of β,γ‐unsaturated α‐ketoester catalyzed by a chiral N,N′‐dioxide‐ZnII complex. Ligand‐accelerated catalysis was found, and a possible transition‐state model was proposed to explain the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(12 citation statements)
references
References 77 publications
0
12
0
Order By: Relevance
“…In order to understand the catalytic mechanism, we obtained ac rystal structure of the catalyst. [18] Ther esults show that the tetradentate L 3 -PiEt 2 -1-Ad coordinates to Zn II with two amine oxide oxygen atoms and two amide oxygen atoms.T wo water molecules also occupy two coordination sites,forming asix-coordinate octahedral complex. Based on the crystal structure of the catalyst, as well as the determination of absolute configuration of products,apossible transition-state model was proposed to explain the origin of the stereoinducement (Scheme 3).…”
Section: Angewandte Chemiementioning
confidence: 97%
“…In order to understand the catalytic mechanism, we obtained ac rystal structure of the catalyst. [18] Ther esults show that the tetradentate L 3 -PiEt 2 -1-Ad coordinates to Zn II with two amine oxide oxygen atoms and two amide oxygen atoms.T wo water molecules also occupy two coordination sites,forming asix-coordinate octahedral complex. Based on the crystal structure of the catalyst, as well as the determination of absolute configuration of products,apossible transition-state model was proposed to explain the origin of the stereoinducement (Scheme 3).…”
Section: Angewandte Chemiementioning
confidence: 97%
“…Zn(OTf) 2 (10 mol%) + 82 81 In the same year, these authors also reported an enantioselective domino reaction of β,γ-unsaturated α-ketoesters 10 with diazoimides 99 promoted at 30 °C in 1,2-dichloroethane (DCE) as solvent through bimetallic relay catalysis using an achiral rhodium complex, such as dirhodium tetrapivalate (Rh 2 Piv 4 ) (0.5 mol%), and a chiral zinc catalyst in situ generated from 10 mol% of Zn(OTf) 2 and 10 mol% of chiral N,N'-dioxide ligand 100 [64]. The rhodium catalyst allowed to generate a carbonyl ylide intermediate from the diazoimide which subsequently reacted through asymmetric [4+3] cycloaddition with the β,γ-unsaturated α-ketoester catalyzed by the chiral zinc complex.…”
Section: Reactions Using Nn'-dioxide Ligandsmentioning
confidence: 99%
“…Recently, Feng has shown that the combination of Zn(OTf) 2 and a chiral ligand along with Rh 2 (piv) 4 can enable the construction of complex oxa-bridged oxazocines, 6.6c, setting three chiral stereocenters in one step under mild conditions (Scheme 6.6). 68 The diazoimide 6.6a loses N 2 and forms a Rh-carbene. This can then cyclize to form an isomünchnone, which acts as a 1,3-dipole.…”
Section: Dual-activation Modesmentioning
confidence: 99%